Case report and literature review: Acute rhabdomyolysis caused by overheating of electric blanket complicated with Guillain-Barré syndrome - Jiang, Dongyang; Zhao, Ming; Li, Xiaojun; Hu, Qiongdan; Zhang, Qiong (Frontiers in Neurology, 2024)
Rhabdomyolysis (RM) induced by electric blankets is exceedingly rare, with only three cases identified in our literature review. Both RM and Guillain–Barré syndrome (GBS) present with similar clinical manifestations of myalgia and muscle weakness, posing a potential challenge for accurate diagnosis in clinical settings. This report presents the case of a 22-year-old man who developed RM subsequent to the use of an electric blanket. Despite undergoing plasma exchange and renal replacement therapy, the patient continued to exhibit poor muscle strength in both lower limbs. Subsequent comprehensive evaluation revealed the presence of concurrent GBS. Following a 5-day course of intravenous gamma globulin treatment, the patient experienced rapid recovery of muscle strength and was discharged. Additionally, we reviewed seven cases from the literature of coexistent RM and GBS. This indicated that investigation of the timing of onset of muscle strength decline in RM patients could help to identify potential concurrent neurological or muscular disorders. In cases in which concurrent GBS and RM cannot be definitively ascertained during early hospitalization, prioritizing plasma exchange treatment may lead to improved patient outcomes.